2002
DOI: 10.1007/s00213-002-1192-1
|View full text |Cite
|
Sign up to set email alerts
|

Orphanin FQ/nociceptin blocks cocaine-induced behavioral sensitization in rats

Abstract: Rationale-Orphanin FQ/nociceptin (OFQ/N), the endogenous ligand of the opioid receptor-like (ORL-1) receptor, shows similarities to dynorphin A (1−17) in structure and functions. Dynorphin and other kappa opioid receptor agonists have been shown to block cocaine sensitization.Objective-The present study was designed to examine the ability of OFQ/N to block cocaineinduced behavioral sensitization.Methods-Rats were habituated to testing chambers for 1 h, injected with artificial cerebrospinal fluid (aCSF) or OFQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 45 publications
3
35
0
Order By: Relevance
“…The previous study used a protocol of chronic cocaine infusion known to produce tolerance to the motor stimulatory action of cocaine (King et al 1992;Reith et al 1987). On the other hand, the present study determined the level of OFQ/N-IR under a repeated cocaine treatment paradigm that induces sensitization to the locomotor stimulatory effects of cocaine (Lutfy et al 2002), which was confirmed in the current study (Fig. 3).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The previous study used a protocol of chronic cocaine infusion known to produce tolerance to the motor stimulatory action of cocaine (King et al 1992;Reith et al 1987). On the other hand, the present study determined the level of OFQ/N-IR under a repeated cocaine treatment paradigm that induces sensitization to the locomotor stimulatory effects of cocaine (Lutfy et al 2002), which was confirmed in the current study (Fig. 3).…”
Section: Discussionsupporting
confidence: 85%
“…For example, we have shown that intra-VTA administration of OFQ/N reduced cocaine-induced motor stimulation and also blocked locomotor sensitization induced by repeated intermittent cocaine administration (Lutfy et al 2002). The current neurochemical data demonstrating that the level of OFQ/N-IR was reduced by acute cocaine treatment raises the possibility that cocaine may cause the release of OFQ/N along the mesocorticolimbic dopaminergic pathway and might be a means through which the action of cocaine can be auto-regulated.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Specifically, in situ hybridization and immunohistochemical studies have demonstrated localization of the ORL-1 receptor in the ventral tegmental area (VTA) Norton et al, 2002), where the cell bodies of the mesolimbic dopaminergic reward circuitry originate. Consistent with its localization, behavioral studies have shown that OFQ/N suppresses basal motor activity (Devine et al, 1996;Lutfy et al, 2001), at least in part, through an action in the VTA (Lutfy et al, 2002;Narayanan et al, 2004). …”
Section: Introductionmentioning
confidence: 93%